Mewujudkan Masyarakat Tertib Administrasi Kependudukan melalui Program Kalimasada di Kelurahan Genting Kalianak, Kota Surabaya - Prameiswary, Adinda; Tukiman, Tukiman (Jurnal Ilmiah Wahana Pendidikan, 2023)
The rapid development of technology requires the government to be more responsive, adaptive and innovative to changes in order to provide excellent public services to the community. The Kalimasada program is a movement to build a government ecosystem that is aware of the importance of population administration which in the process also utilizes digital technology, namely the Klampid New Generation (KNG) application. Through this MSIB program, the author as an apprentice student hopes to show a real contribution to his work in socializing the Kalimasada program to the people of the Genting Kalianak sub-district in order to create an orderly society in population administration.